Research on Historical and Future Spatial-Temporal Variability of Precipitation in China - Jun Yin; Denghua Yan; Zhiyong Yang; Zhe Yuan; Yong Yuan; Hao Wang; Xiaoliang Shi (Advances in Meteorology)
Based on observed data and data simulated by climate models, temporal variation and spatial distribution of precipitation in China from 1961 to 2050 were investigated. The slope of annual precipitation and Mann-Kendall statistical test were applied to quantify the trend magnitude and detect the significant trend, respectively. Besides, decadal and interannual variations of different rain belts were analyzed to reveal the spatial changing pattern of precipitation. Results indicated the following. (1) During 1961–2011, annual precipitation in Haihe River Basin decreased significantly while the annual precipitation in river basins in the northwest increased significantly. Although the annual precipitation of Yangtze River Basin has an indistinctive decreasing trend, that in the middle and lower reaches has increased and that in the upper reaches has decreased. Arid zone and humid zone are shrinking while semiarid and semihumid zone are expanding. Transformation between semiarid and arid zones, humid and semihumid zones is frequent. During 2011–2050, annual precipitation will not change much (−6~12%) except river basins in the southwest (more than 40%) compared with the baseline. Besides, the area of arid zone will decrease and humid zone area will increase. Transformation area between semiarid and arid zone and humid and semihumid zone is small.